GENDER TRANSFORMATIONS IN EMPLOYMENT AS A TOOL FOR INTERNATIONAL INTEGRATION OF THE UKRAINIAN LABOR MARKET IN THE CONTEXT OF THE RUSSIAN-UKRAINIAN WAR - Mykhailyshyn, L. I.; Korovchuk, Y. I.; Hrushko, O. D. (The actual problems of regional economy development, 2024)
The study examines the peculiarities of gender transformations as an instrument of international integration of the Ukrainian labor market in the context of the russian-Ukrainian war. The features of transformations, the pre-war and post-war state of the Ukrainian labor market are identified. The study's findings demonstrate that during the pre-war years, the Ukrainian labor market strongly impacted the international (in particular, European) labor market. With the outbreak of war, this impact increased significantly due to large-scale flows of refugees from the entire country. The authors provide a summary of the objective and forced reasons for the increase in the existing socio-economic factors of migration, among which the following are particularly noticeable destruction of economic facilities, damage to infrastructure, loss of supply of goods, decline in aggregate consumer demand, increased need for security, additional social protection, rehabilitation, and education. It is proved that the labor market of Ukraine in the conditions of war has become a donor of the skilled and highly productive workforce for the EU countries, resulting in its transformation from a model of labor excess to a model of labor deficit. It is noted that mass migration due to the abovementioned reasons was not the only factor that caused significant changes in the Ukrainian labor market. In addition, the negative trends in the development of Ukraine's labor market and the resulting decline in its integration potential were formed exclusively by military factors: the occupation of millions of Ukrainians, the mobilization of the men's population with subsequent recruitment into the Armed Forces or volunteering, and the increase in mortality among the working-age military and civilians. As a result, a significant reduction in the offer of workforce in the Ukrainian labor market has been noted, and given the urgency of restoring this resource, the negative impact of these changes will be observed in the Ukrainian economy for a long period. Based on these conditions, the author substantiates the need to develop measures and implement several necessary reforms aimed at overcoming gender imbalances in various areas of employment in Ukrainian society. Such measures will contribute to stabilizing the domestic labor market for the post-war reconstruction of the country and will ensure the preservation of the identity of Ukraine and the Ukrainian nation.